Integrated Contextual Learning and Food Science Students' Perception of Work Readiness - Coorey, Ranil; Firth, Ann (Institute of Food Technologists, 2013)
The expectation that universities will produce graduates with high levels of work readiness is now a commonplace in government policies and statements from industry representatives. Meeting the demand requires that students gain industry related experience before graduation. Traditionally students have done so by undertaking extended work placements. With increasing numbers of students competing for a limited number of placements, virtual and simulated work environments are becoming popular alternative strategies. This paper describes the simulation of workplace practices through the introduction of integrated contextual learning (ICL) into the Food Science Program at Curtin Univ. as a way of enhancing employability and increasing students’ confidence that they are work ready.